Peran TPQ dalam Meningkatkan Kualitas Kemampuan Baca Al-Qur’an pada Anak: Studi Kasus di TPQ Darul Fallah 2 Japanan Mojowarno Jombang - Eny Fatimatuszuhro Pahlawati; Eko Hadi Wardoyo; Putri Maulida (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study aims to determine the role of TPQ in improving the quality of children's Qur'an reading ability at TPQ Darul Fallah 2 Japanan Mojowarno Jombang. This study uses a qualitative descriptive approach. Data collection uses observation, interview and documentation techniques with deductive and inductive analysis techniques. The results of the study indicate that the role of the Al-Qur'an Education Park (TPQ) Darul Fallah 2 in improving the quality of children's ability to read the Qur'an is very significant. TPQ Darul Fallah 2 has several key elements that support the success of the learning process, including careful planning, the presence of teachers who live in one village, the preparation of a flexible curriculum, and the use of a structured tilawati learning method. In addition, adequate facilities and infrastructure and periodic learning evaluations also play an important role in achieving optimal results. Keywords: TPQ Darul Fallah 2; Qur'an Reading Ability; Children